New synonymy, new combinations and other taxonomic changes in Japanese xyleborine ambrosia beetles (Coleoptera: Curculionidae: Scolytinae) - Smith, Sarah M.; Beaver, Roger A.; Cognato, Anthony I. (Zootaxa, 2018)
The following 13 new combinations are given: Ambrosiophilus osumiensis (Murayama, 1934), Ancipitis machili (Niisima, 1910), Cyclorhipidion bispinum (Nobuchi, 1981), Cyclorhipidion japonicum (Nobuchi, 1981), Cyclorhipidion laetum (Niisima, 1909), Cyclorhipidion misatoense (Nobuchi, 1981), Cyclorhipidion miyazakiense (Murayama, 1936), Cyclorhipidion okinosenense (Murayama, 1961), Cyclorhipidion takinoyense (Murayama, 1953), Debus defensus (Blandford, 1894), Immanus permarginatus (Schedl, 1933), Microperus calamoides (Murayama, 1934), Microperus quercicola (Eggers, 1926), all originally described in Xyleborus Eichhoff, 1864. The following 24 new synonyms are proposed: Ambrosiophilus atratus (Eichhoff, 1876) (=Xyleborus collis Niisima, 1910 syn. n.); Ambrosiophilus osumiensis (Murayama, 1934) (=Xyleborus metanepotulus Eggers, 1939 syn. n.); Ancipitis machili (Niisima, 1910) (=Xyleborus depressus Eggers, 1923 syn. n.; = Xyleborus kojimai Murayama, 1936 syn. n.); Anisandrus dispar (Fabricius, 1792) (=Xyleborus ishidai Niisima, 1909 syn. n.); Cnestus aterrimus (Eggers, 1927) (=Cnestus maculatus Browne, 1983 syn. n.; = Cnestus murayamai Schedl, 1962 syn. n.; = Cnestus murayamai Browne, 1963 syn. n.; = Tosaxyleborus pallidipennis Murayama, 1950. syn. n.); Cyclorhipidion miyazakiense (Murayama, 1936) (=Xyleborus armipennis Schedl, 1953 syn. n.; = Xyleborus wakayamensis Nobuchi, 1981 syn. n.); Microperus kadoyamaensis (Murayama, 1934) (=Xyleborus nameranus Murayama, 1954 syn. n.); Microperus quercicola (Eggers, 1926) (=Xyleborus izuensis Murayama, 1952 syn. n.); Planiculus bicolor (Blandford, 1894) (=Xyleborus ashuensis Murayama, 1954 syn. n.); Xyleborinus attenuatus (Blandford, 1894) (=Xyleborinus canus Niisima, 1909 syn. n.); Xyleborinus schaufussi (Blandford, 1894) (=Xyleborus kraunhiae Niisima, 1910 syn. n.); Xyleborus festivus Eichhoff, 1876 (=Xyleborus detectus Schedl, 1975a syn. n.; = Xyleborus pinicola Eggers, 1930 syn. n.; = Xyleborus pinivorus Browne, 1980 syn. n.); Xyleborus metacuneolus Eggers, 1940 (= Xyleborus kaimochii Nobuchi, 1981 syn. n.); Xyleborus perforans (Wollaston, 1857) (=Xyleborus shionomisakiensis Murayama, 1951 syn. n.); Xyleborus pfeilii (Ratzeburg, 1837) (=Xyleborus septentrionalis Niisima 1909 syn. n.); Xyleborus seriatus Blandford, 1894 (=Xyleborus todo Kono, 1938 syn. n.); Xylosandrus brevis (Eichhoff, 1877) (=Xyleborus montanus Niisima, 1910 syn. n.). Arixyleborus yakushimanus (Murayama, 1958) is removed from synonymy with A. malayensis (Schedl, 1954). The types of Xyleborus nagaoensis Murayama, 1934, and X. ohtoensis Nobuchi, 1981 were examined and are confirmed to be correctly placed in Xyleborus. Lectotypes are designated for Xyleborus ishidai Niisima, 1909, and Xyleborus septentrionalis Niisima, 1909.